A new Phylloporus from two relict Fagus grandifolia var. mexicana populations in a montane cloud forest - Leticia Montoya Bello; Víctor Manuel Bandala Muñoz (Mycotaxon, 2011)
A new species, Phylloporus fagicola, has been discovered growing in association with two relict populations of Fagus grandifolia var. mexicana in the subtropical region of central Veracruz (eastern Mexico). e species belongs to a taxonomic group characterized by broadly ellipsoid oblong to ovoid basidiospores, distinct from the subfusoid boletoid type. e new taxon is described, illustrated, and compared with closely similar species.